Irish Intellectual Disability Services for Children and Austerity Measures: The Qualitative Impact of Recession through Framework Method - Flynn, Susan (My University, 2021)
Intellectually disabled children experience unique vulnerabilities related to poverty. The literature further identifies strong concerns for service delivery and practice with intellectually disabled children in the context of austerity measures arising from economic recession. Statistical data in Ireland are well developed on the equality impacts of economic recession in 2008. Qualitative research is by comparison lacking. This study presents research findings on the impact of recession on intellectually disabled young people and their families in Ireland. It does so to illuminate the meaning of existing statistical indicators which suggest adverse effects of austerity on this population group. A Framework Method of analysis is applied to transcripts produced from a Biographical Narrative Interpretative Method (BNIM) of interviewing. A sample of eight participants is reported on, which includes two intellectually disabled young people, three parents of intellectually disabled young people and three social workers in disability services. Findings take the form of themes and subthemes, which are then used to inform a discussion on key learning for practitioners moving forward. Within this, distinct concerns for practice with intellectually disabled children and young people are identified, such as the potential for practitioners to mis-conceptualise some behaviours that challenge as arising from impairment rather than poverty. Overall a predominantly negative impact of austerity on these families is evidenced. Results indicate that more meaningful partnership between policy makers and service users is required in future periods of economic adversity.
PUBLISHED
Keywords: Economic recession; Austerity; Disability; Social work; Children; Inclusive Society; Families & Social Change; Social Work